2017
DOI: 10.1093/ejcts/ezx119
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-developmental outcome in single-ventricle patients: is the Norwood procedure a risk factor?

Abstract: Neuro-developmental outcome of preschool-aged Fontan patients was in the normal range. The Norwood procedure was not a risk factor for neuro-developmental impairment. Preoperative condition and patient-related factors were more important determinants than variables related to surgical palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Our finding that HC at birth is an important predictor of IQ confirms previous studies that have demonstrated a relationship between poor fetal head growth 35 or small HC at birth and neurodevelopmental outcome in early childhood, 6,10,13,15,16,18 pre-school age, 11,17 and adolescence. 14 There is consistent evidence that intrauterine brain growth is altered in children with complex CHD, starting at around 30 weeks gestation, 29 resulting in smaller HC and smaller brain volumes at birth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that HC at birth is an important predictor of IQ confirms previous studies that have demonstrated a relationship between poor fetal head growth 35 or small HC at birth and neurodevelopmental outcome in early childhood, 6,10,13,15,16,18 pre-school age, 11,17 and adolescence. 14 There is consistent evidence that intrauterine brain growth is altered in children with complex CHD, starting at around 30 weeks gestation, 29 resulting in smaller HC and smaller brain volumes at birth.…”
Section: Discussionsupporting
confidence: 91%
“…38 We found postoperative ICU stay to strongly predict IQ. This potentially modifiable risk factor has been identified by many studies, 10,17,39 and may be a surrogate marker for surgical and postoperative complexity with negative impact on later neurodevelopmental outcome. 20 A variety of other risk factors for poor IQ have been identified in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, much research has been done on children undergoing cardiac surgery on CPB, and many have found that certain on‐pump procedures are linked to increased risk of stroke, cerebral changes, cognitive impairment, and/or neurodevelopmental disability 39‐44 . However, the literature is not unanimous on this topic either, and some studies have reported no increased risk of neurodevelopmental impairment after such procedures 45 . Postoperative movement disorders like chorea have also been reported following CPB, and may be related to on‐pump time 46‐49 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Developmental problems, including cognitive impairment, fine and gross motor deficits, and speech and language disorders, are common especially in children with complex CHD requiring corrective or palliative surgery during the neonatal period. [1][2][3][4] However, cognitive abnormalities, often to a milder degree, are also found in children with less complex CHD undergoing surgery beyond the neonatal period. 1,[5][6][7][8] Developmental impairment observed in children with CHD is multifactorial and is influenced by nonmodifiable patient-specific factors and potentially modifiable factors including surgical technique and perioperative care.…”
Section: Introductionmentioning
confidence: 99%